Fiscal Transfers, Horizontal Equity and Post-Secondary Education - Hum, Derek; Strain, Frank (Canadian Journal of Higher Education, 1988)
Horizontal equity is interpreted to mean that equals in different provinces should be treated equally. We argue that current arrangements for government funding of post-secondary education in Canada are flawed because they contain provisions which perpetuate disparities in the treatment of Canadians by province of residence. Current arrangements are criticized for inadequate equalization and lack of expenditure standards. An education-needs adjustment factor is suggested. Fiscal equity strives to ensure that citizens in all provinces have access to comparable services and bear comparable tax burdens. The cost of services is conditional on the expenditure standard selected and the number of beneficiaries. The capacity to provide the service is related to the population and wealth of the province. Accordingly, our suggested amendment incorporates all these elements; it allows greater fiscal transfers to provinces experiencing greater need and/or smaller tax bases.